2010
DOI: 10.1158/1535-7163.mct-09-0815
|View full text |Cite
|
Sign up to set email alerts
|

BNC105: A Novel Tubulin Polymerization Inhibitor That Selectively Disrupts Tumor Vasculature and Displays Single-Agent Antitumor Efficacy

Abstract: Vascular disruption agents (VDA) cause occlusion of tumor vasculature, resulting in hypoxia-driven tumor cell necrosis. Tumor vascular disruption is a therapeutic strategy of great potential; however, VDAs currently under development display a narrow therapeutic margin, with cardiovascular toxicity posing a dose-limiting obstacle. Discovery of new VDAs, which display a wider therapeutic margin, may allow attainment of improved clinical outcomes. To identify such compounds, we used an in vitro selectivity scree… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
93
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 18 publications
1
93
0
Order By: Relevance
“…8 Efficacy in response to BNC105P (the clinically used prodrug of BNC105) has been shown in breast and lung cancer xenograft models. 8,9 The firstin-human clinical trial of BNC105P in solid tumors revealed on-target action of the drug with tubulin disruption seen in a surrogate tissue, peripheral blood mononuclear cells (PBMCs). In this study, 4 of 21 patients with advanced and/or metastatic solid tumors achieved stable disease with the single agent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Efficacy in response to BNC105P (the clinically used prodrug of BNC105) has been shown in breast and lung cancer xenograft models. 8,9 The firstin-human clinical trial of BNC105P in solid tumors revealed on-target action of the drug with tubulin disruption seen in a surrogate tissue, peripheral blood mononuclear cells (PBMCs). In this study, 4 of 21 patients with advanced and/or metastatic solid tumors achieved stable disease with the single agent.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, it has not been tested for efficacy in liquid malignancies. Here, we have determined that BNC105 potently and acutely induces cell death in CLL cells through JNK activation and induction of Noxa at concentrations much lower than either vinblastine or CA4.…”
mentioning
confidence: 99%
“…1,2 VDAs cause the relatively fast growing and chaotic tumor vasculature to collapse, ceasing tumor blood perfusion with subsequent tumor ischemia, hypoxia and necrosis. VDAs achieve immediate vascular damage and are suited to acute administration regimens, 3 distinct from anti-angiogenic agents such as bevacizumab which require longer term administration.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 It is thought that the viable cells within the tumor rim activate a suite of adaptive and survival mechanisms implicit to many tumors and are responsible for driving the recovery of the tumor from the VDA treatment. 5,6,7 Given the propensity of tumors to recover from the effects of VDA action, clinical development has sought to investigate agents to use in combination with VDA treatment regimens.…”
Section: Introductionmentioning
confidence: 99%
“…The latter compound has been reported to currently be in phase III evaluation (clinical trial no. NCT00699517) for the treatment of advanced-stage soft tissue sarcoma, following the failure of anthracycline and ifosfamide chemotherapies (17).…”
Section: Discussionmentioning
confidence: 99%